2019
DOI: 10.1007/978-3-030-36365-9_26
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Saudi Stock Market Index by Incorporating GDELT Using Multivariate Time Series Modelling

Abstract: Prediction of financial and economic markets is very challenging but valuable for economists, business owners, and traders. Forecasting stock market prices depends on many factors, such as other markets' performance, economic state of a country, and others. In behavioral finance, people's emotions and opinions influence their transactional decisions and therefore the financial markets. The focus of this research is to predict the Saudi Stock Market Index by utilizing its previous values and the impact of peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…: White noise, which is a time series that includes other effects on the series , It is a series independent of the series . There are some difficulties with the ARIMAX model defined in formula (2) is that the conversion function may contain an unlimited number or a large number of parameters. The number of parameters of the input and output series parameters is specified while another formula for the ARIMAX model is being developed.…”
Section: B Autoregressive Integrated Moving Averagementioning
confidence: 99%
See 2 more Smart Citations
“…: White noise, which is a time series that includes other effects on the series , It is a series independent of the series . There are some difficulties with the ARIMAX model defined in formula (2) is that the conversion function may contain an unlimited number or a large number of parameters. The number of parameters of the input and output series parameters is specified while another formula for the ARIMAX model is being developed.…”
Section: B Autoregressive Integrated Moving Averagementioning
confidence: 99%
“…However, the test results indicated that the time series reach the stationary stage after Taking the first differences of both series, as the value of the significance levels is less than (0.05). The output and input series are drawn after taking the first differences to confirm stationary, as shown in Figure (2). Furthermore, the ACF coefficients for the two series are plotted in Figure (3)…”
Section: A Description Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, few scholars have discussed how to predict the Tadawul index (TASI) using some specific factors [12,[45][46][47]. Alsufyani and Sarmidi [48] found there is no relation between commodity energy price and TASI volatility.…”
Section: Tadawul Index (Tasi) and International Indicesmentioning
confidence: 99%
“…The reasons are that the interactions of multi-factors walk in line and across each other, which makes the goal of reaching a proper estimate truly challenging. Market economic factors, interaction between stock markets, and international variables are some instances of these concerned factors [12]. Unsurprisingly, specific movements of market indices may influence investors to buy, sell, or hold, especially if these occurrences take place at the right time.…”
Section: Introductionmentioning
confidence: 99%